Secularization, Laicism, and Religious Rundamentalism in Contemporary Societies: Reflections from Latin America - Pineda Sancho, Andrey (2018)
For the past few decades the western world has seen a particular religious revival. Far from disappearing from the social-political scenarios or from the immediate vital scope of the population, religion has not only maintained much of its long-standing social power, but it has also found new routes of expression. However, this has happened at the same time as the decline of the social-cultural influence of outdated religious institutions and the general transformation of belief structures. Although the world today has a much more robust and varied religious offer, it cannot be denied this diversity has brought on a relativization of the different beliefs, as well as the possibility that these will not necessarily be under the control of the institutions that, throughout history, have aimed to control their content. Thus, this article intends to offer a gateway to help understand the confluence of the two trends described, and which is also apt to escape from the empirical contradictions these seem to suggest.